Sinä päivänä kun synnyin (vol. 1) - Ultra Bra (yhtye); Hovatta, Vuokko, 1972-; Karjalainen, Mikko, 1974-; Kokkonen, Terhi, 1974-; Koskinen, Kerkko, 1973-; Lassy, Timo, 1974-; Lehtinen, Antti, 1973-; Leppälä, Kari; Melasniemi, Joel, 1975-; Pelttari, Kari; Pethman, Jan; Pohjanheimo, Petriikka; et al. ([Suomi] : Ainoa Productions Oy, 2017)
21 kappaletta.
Ultra Bra (yhtye): Vuokko Hovatta (lauluääni), Terhi Kokkonen (lauluääni), Anna Tulusto (lauluääni, Levy 2, A1), Pohjanheimo Petriikka (lauluääni), Arto Talme (lauluääni), Olli Virtaperko (lauluääni), Kerkko Koskinen (piano), Antti Lehtinen (rummut), Joel Melasniemi (kitara), Jan Pethman (lyömäsoittimet), Tommi Saarikivi (sähköbasso), Kari Pelttari (trumpetti), Ilmari Pohjola (pasuuna), Marko Portin (saksofoni), Mikko Karjalainen (trumpetti), Timo Lassy (saksofoni), Leppälä, Kari (sähköbasso), Anssi Sopanen (rummut).
Keywords: Ultra Bra (yhtye) -- kokoelmat; laulelmat; popmusiikki; poliittiset laulut